2014
DOI: 10.1080/09692290.2013.860612
|View full text |Cite
|
Sign up to set email alerts
|

In the Shadow of Basel: How Competitive Politics Bred the Crisis

Abstract: What if global governance mechanisms undermine the capacity of national banking regulators to deal with the deviant activities of their banks? Such was the case, this paper argues with respect to the Basel Accords and the regulation of the bank-based shadow-banking system. Securitizationactivities by banks, driven by regulatory arbitrage have been an integral part of the shadow banking sector and a central transmission mechanism during the financial crisis. They have been identified as problematic by the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 46 publications
0
45
0
1
Order By: Relevance
“…This strategy was, for example, the choice of East Asian emerging market regulators in implementing the Basel I Accord (Walter 2008, Chey 2013. Likewise, Thiemann's (2014) already cited study on the interaction between national accounting rules and banking laws on the one hand and transnational regulatory standards of the Basel I Accord on the other hand, has revealed how eight out of ten analysed OECD countries knowingly oversaw regulatory arbitrage strategies by banks in their jurisdictions. As we discussed before, Thiemann argues that regulators feared that global market reach would pull financial activity into other jurisdictions if the regulator were to push legislation or regulation beyond the perforated global Basel standards.…”
Section: Evolution Of the Basel Committeementioning
confidence: 95%
“…This strategy was, for example, the choice of East Asian emerging market regulators in implementing the Basel I Accord (Walter 2008, Chey 2013. Likewise, Thiemann's (2014) already cited study on the interaction between national accounting rules and banking laws on the one hand and transnational regulatory standards of the Basel I Accord on the other hand, has revealed how eight out of ten analysed OECD countries knowingly oversaw regulatory arbitrage strategies by banks in their jurisdictions. As we discussed before, Thiemann argues that regulators feared that global market reach would pull financial activity into other jurisdictions if the regulator were to push legislation or regulation beyond the perforated global Basel standards.…”
Section: Evolution Of the Basel Committeementioning
confidence: 95%
“…Recently, studies even claim that global governance 4 REVIEW OF INTERNATIONAL POLITICAL ECONOMY creates additional problems, rather than reducing the existing ones. Thiemann (2014) demonstrated that the Basel I Accord had loopholes which neglected the usage of special purpose vehicles (an instrument used to circumvent regulations). Yet, even though national regulators became aware of this, they refrained from filling these loopholes.…”
Section: Global Regulation and Asymmetric Influencementioning
confidence: 98%
“…Fourth and finally, the consensus view in the emergent economic and financial literature, and certainly in the policy debate on the origins of shadow banking, suggests that shadow banking is an outcome of regulatory arbitrage in the international finance (Thiemann 2014). In this framework, shadow banking operations offer 'alternative, unregulated means to traditional banking functions' (McIntire 2014: 6).…”
Section: The Role Of Shadow Banking In the Crisis Of 2007-9mentioning
confidence: 99%